2020
DOI: 10.1523/jneurosci.0120-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the Neural Correlates of Perceptual Awareness and Postperceptual Processing

Abstract: To identify the neural correlates of perceptual awareness, researchers often compare the differences in neural activation between conditions in which an observer is or is not aware of a stimulus. While intuitive, this approach often contains a critical limitation: to link brain activity with perceptual awareness, observers traditionally report the contents of their perceptual experience. However, relying on observers' reports is problematic because it is difficult to know whether the neural responses being mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(130 citation statements)
references
References 48 publications
17
95
0
Order By: Relevance
“…The P300 has repeatedly been demonstrated to depend on report requirements in visual tasks (Cohen et al, 2020;M. Pitts, Padwal, Fennelly, Martinez, & Hillyard, 2014;Schlossmacher et al, 2020) and we show that the same is true in the somatosensory domain.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The P300 has repeatedly been demonstrated to depend on report requirements in visual tasks (Cohen et al, 2020;M. Pitts, Padwal, Fennelly, Martinez, & Hillyard, 2014;Schlossmacher et al, 2020) and we show that the same is true in the somatosensory domain.…”
Section: Discussionsupporting
confidence: 70%
“…Most notably, in a series of studies, Pitts and colleagues have demonstrated that the visual P300 only indexes conscious perception when stimuli are reported, i.e. when 3 they are behaviourally relevant to the task (Cohen, Ortego, Kyroudis, & Pitts, 2020;M. A. Pitts, Metzler, & Hillyard, 2014;Schlossmacher, Dellert, Pitts, Bruchmann, & Straube, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…No report paradigms have raised interesting questions regarding the relationship between attention and consciousness (M. A. Cohen, Ortego, Kyroudis, & Pitts, 2020;Frassle et al, 2014;Montemayor & Haladjian, 2019;Wilke et al, 2009). For example, eliminating report also challenges whether the (low frequency) gamma activity that has been associated with consciousness might be related to post-perceptual decision making and/or motor planning instead (Pitts, Padwal, Fennelly, Martinez, & Hillyard, 2014).…”
Section: Outlook 2: Developments Towards An Empirically-testable Quanmentioning
confidence: 99%
“…Thus, AB-related differences in late-stage T1 processing are not consistently observed across studies. Notably, a novel line of evidence suggests that the P3b component does not track perception and encoding, but rather post-perceptual processes (e.g., decision making) (Cohen et al, 2020;Pitts, Martínez, & Hillyard, 2012;Pitts, Padwal, Fennelly, Martínez, & Hillyard, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of stimuli such that they can be reported is typically associated with a late (300-500ms) broadly distributed positive P3 ERP component (Cohen, Ortego, Kyroudis, & Pitts, 2020;Dehaene & Changeux, 2011;Derda et al, 2019;Sigman & Dehaene, 2008). For example, it has been shown that only seen T2s elicit a P3 (Vogel, Luck, & Shapiro, 1998).…”
Section: Erp Analysesmentioning
confidence: 99%